On a Five-Dimensional Chaotic System Arising from Double-Diffusive Convection in a Fluid Layer. (7th March 2013) - Idris, R.; Siri, Z.; Hashim, I.
Abstract : A chaotic system arising from double-diffusive convection in a fluid layer is investigated in this paper based on the theory of dynamical systems. A five-dimensional model of chaotic system is obtained using the Galerkin truncated approximation. The results showed that the transition from steady convection to chaos via a Hopf bifurcation produced a limit cycle which may be associated with a homoclinic explosion at a slightly subcritical value of the Rayleigh number.